Comparison of post-operative outcomes of enhanced recovery after surgery protocol in laparoscopic cholecystectomy with the traditional methods of recovery: A prospective comparative study - Akshita Yadav; Rajesh Angral; Raj Rishi Sharma; Sarvesh Singh Lobana (Asian Journal of Medical Sciences, 2025)
Background: Enhanced recovery after surgery (ERAS) can significantly decrease the length of hospital stay, lessen complications, prejudice the rehospitalization rate, and cut down hospitalization costs. ERAS protocols in laparoscopic surgery have not been fully researched in the Indian setting, especially in government medical colleges. Considering that Indian Hospitals and Government Medical Colleges are already overburdened and overcrowded, ERAS can help alleviate the stress on the hospitals by facilitating early discharges. It is of extreme importance that we have good data and research on the use of ERAS protocols in GMCs and other government hospitals. Aims and Objectives: The aims and objectives of this study were to compare the post-operative outcomes of ERAS protocol in laparoscopic cholecystectomy with the traditional methods of recovery. Materials and Methods: Using convenient sampling patients undergoing laparoscopic cholecystectomy were randomized and divided into two groups: the ERAS group and the traditional Group. Results: The mean length of stay (LOS) was 19.06 h (10.50 SD) in the ERAS group versus 57.17 h (8.89 SD) in the traditional group (P<0.0001 using the unpaired t-test). The mean Visual Analog Scale was 3.65 (2.28 SD) in the ERAS group versus 6.95 (1.63SD) in the traditional group (P=0.0078 using the unpaired t-test). Clinically significant post-operative nausea and vomiting (PONV) was seen in 4 out of 92 patients (8.3%) in the ERAS group versus 20 of the 92 patients (21.7%) in the traditional approach. Conclusion: Our findings reinforce the notion that the traditional approach of peri-operative care is associated with worse outcomes and ERAS protocols improve PONV and post-operative pain and decrease the LOS.